Effect of Sc addition on the microstructure and mechanical properties of as-atomized and extruded Al–20Si alloys - Kilicaslan, M. Fatih; Lee, Woo Ram; Lee, Tae Haeng; Sohn, Yongho; Hong, Soon Jik (Elsevier BV, 2012)
Abstract The microstructure evolution and mechanical properties of Al–20Si alloy with Sc addition were investigated after as-atomized and hot-extruded conditions. Microstructural and spectroscopic analyses demonstrate that Sc is enriched at the Si/Al interface. It could be observed that the presence of Sc refined the size of the primary and eutectic Si, without significantly affecting the shape. A considerable improvement in tensile strength, compressive strength, and elongation was observed due to addition in Sc percentage into the composition. The correlation between the microstructure and mechanical behavior strongly indicates that the addition of Sc modifies the Si particles by impurity induced twinning (IIT) mechanisms.
Keywords: Multidisciplinary; ZR; Physics; Materials Science; Polycrystalline film; Gas atomization; Grain boundary; Diffusion; Atom probe tomography; Triple junction; Al-Si alloys; Applied; Powder technology; SILICON; Rapid solidification; 8. Economic growth